(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Banks form a fundamental component of the financial system and also active players infinancial markets. An efficient banking system capable of mobilizing the savings and channeling them toproductive purposes are essential for the development of any economy. In present dynamic andcompetitive financial environment, it is necessary to find out strength and weaknesses of banks, to facechallenges effectively Research in financial area becomes helpful for bank to take better decision.The objective of the study is to analyze and compare the overall financial performance of selected publicand private sector banks in India. The study is based on secondary data that has been collected fromannual reports of the banks, Reserve Bank of India website. Financial performance of banks has beenjudged on the basis of seven selected financial ratios i.e. Capital Adequacy ratio, Return on Equity, NPA toNet advance ratio, Total Expenditure to Total Income ratio, Total Advance to Total Deposits ratio, NetInterest Margin, Return on Average Assets. Top ten public and private sector banks have been selectedfor the study.Data have been collected for four years i.e.F.Y. 2015-16,2016-17, 2017-18, 2018-19. Average of four yearshave been calculated for each ratio of public and private sector banks. Further, comparison of financialperformance of public and private sector bank has been made on the basis of average ratios. T-Test havebeen used for hypotheses testing. Financial ratios i.e. Capital Adequacy ratio, Return on Equity, NPA toNet advance ratio, Total Expenditure to Total Income ratio, Total Advance to Total Deposits ratio, NetInterest Margin, Return on Average Assets of private sector banks are showing better results ascompared to public sector banks. Analysis and interpretation of data has proven that financialperformance of private sector banks is better than public sector banks. Public sector banks need toimprove in areas of Capital Adequacy ratio, Return on Equity, NPA to Net advance ratio, Return onAverage Assets for better financial performance in future.